The Humane Society of the Commonwealth of Massachusetts : an historical review, 1785-1916 - Howe, M. A. De Wolfe (Mark Antony De Wolfe), 1864-1960 (Printed for the Humane Society at the Riverside Press, 1918)
Contains a history of the Humane Society which became the United States Life-Saving Service and the beginning of the United States Coast Guard.